The Effect of Synbiotic Intervention on Oral Microbiota and Inflammatory Markers in a Rat Model of Chemotherapy-Induced Mucositis - Anantha Sena; Ambar Mudigdo; Irma Isnafia Arief; Dono Indarto (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study evaluated the effects of synbiotic yogurt containing Lactobacillus plantarum and Roselle extract on oral microbiota, inflammation (IL-1β levels), and body weight in a rat model of chemotherapy-induced oral mucositis. IL-1β levels in serum showed a statistically significant difference between the oral mucositis (PC) and synbiotic-treated (T) groups (p = 0.025). The bacterial count revealed a decrease in beneficial lactic acid bacteria in the PC group (2 log CFU/g), while pathogenic Escherichia coli and Staphylococcus aureus increased. In the T group, synbiotics partially restored lactic acid bacteria (4 log CFU/g), though pathogenic levels remained elevated. Body weight analysis showed significant weight loss in both groups, with synbiotic treatment resulting in slightly less weight loss compared to the PC group. While synbiotics improve microbial balance, prolonged treatment may be needed for more substantial reductions in pathogenic bacteria and better maintenance of body weight.